Hypothyroidism Causing Precocious Puberty and Ovarian Torsion - Kini, Sandesh; Bhat Y, Ramesh; Kousika, Phalguna; Thunga, Chennakeshava; Handattu, Koushik; Karegowda, Lakshmikanth Halegubbi (Journal of Nepal Paediatric Society, 2019)
Hypothyroidism in children causes delayed puberty. However longstanding untreated hypothyroidism can lead to precocious puberty which may be secondary to hyperprolactinemia or increased levels of thyroid stimulating hormone (TSH), enhancing the sensitivity of ovaries to circulating gonadotropins. Here we report a seven and half years old girl with hypothyroidism presenting with precocious puberty and multicystic ovaries which responded well to thyroid hormone supplementation but subsequently developed left ovarian torsion requiring surgical intervention.